Immunological responses against vancomycin-resistant Enterococcus faecium and Enterococcus faecalis by mice. Issue 2 (4th March 2018) - Cho, Yun Sang; Lee, Mun Han; Kim, Jong Man; Lee, Hee Soo; Yoo, Han Sang; Park, Yong Ho; Ryu, Pan Dong
ABSTRACT: Methicillin-resistant Staphylococcus aureus (MRSA) infections in humans can currently only be treated with vancomycin. Consequently, vancomycin-resistant Enterococcus spp. pose a serious public health hazard because MRSA can acquire their vancomycin resistance. While the microbiological and genetic characteristics of vancomycin-resistant enterococci (VRE) have been extensively studied, serological diagnostic tools for these organisms are lacking. The VanA and VanB classes of VRE show marked resistance. Here, we identified the VanA and VanB proteins that are immunogenic in mice. To do so, mice were orally infected with a VanA strain of E. faecium or a VanB strain of E. faecalis and the serologically immunogenic proteins were identified by SDS-PAGE and Western blot analysis. The mice reacted to the 27 and 65 kDa cell envelope (CE) proteins of VanA at 1 week post-infection (wpi) and then reacted to the 100 kDa cytoplasmic protein (CP) at 2–4 wpi. With regard to VanB, the mice responded at 1–4 wpi, 3–4 wpi, and 4 wpi to the 70 kDa, 25 and 35 kDa, and 79 kDa CE proteins, respectively, and at 3 wpi to the 39 kDa CP. The identification of these immunogenic proteins may be useful for diagnosing and for producing immunotherapeutic VRE antibodies.